De la Didactique de la langue à la didactique des langues : observation d'un parcours épistémologique - Isabel Alarcão; Ana Isabel Andrade; Maria Helena Araújo e Sá; Sílvia Melo-Pfeifer (Recherches en didactique des langues et des cultures)
The present study aims at systematising and discussing the epistemological evidences of transition from Language Didactics to Plurilingual Didactics, in the three dimensions of this discipline (Alarcão, 1994): research, curricular and professional. Bearing in mind a meta- analysis at a national level, of the Language Didactics group of this institution, (see Alarcão et al, 2004), in which the presence of didactic discourse about plurilingualism was considered one of the identifying traits, we have chosen the post-graduate programme in Language Didactics of the University of Aveiro as the focus of this research. This academic context seems to be particularly suited to the object of study. In the context of the analysed discourse (understood as an interface between production of knowledge, advanced education and reflection about practices), the discussion of results will bring to light the trends of a discipline that seems to be moving towards a "global approach to plurilingual education" (Coste, 2004, editor's translation).